Health and social care professionals’ experiences of providing end of life care during the COVID-19 pandemic: A qualitative study - Hanna, JR; Rapa, E; Dalton, LJ; Hughes, R; Quarmby, LM; McGlinchey, T; Donnellan, WJ; Bennett, KM; Mayland, CR; Mason, SR (SAGE Publications, 2021)
Background: Health and social care professionals’ ability to address the needs of patients and their relatives at end of life is likely to have been impacted by the COVID-19 pandemic. Aim: To explore health and social care professionals’ experiences of providing end of life care during the COVID-19 pandemic to help inform current/future clinical practice and policy. Design: A qualitative interview study. Data were analysed using thematic analysis. Setting/participants: Sixteen health and social care professionals working across a range of clinical settings in supporting dying patients during the first wave (March–June 2020) of the COVID-19 pandemic in the United Kingdom. Results: Participants reported emotional and practical challenges to providing end of life care during the pandemic, including increases in patient numbers, reduced staffing levels and relying on virtual platforms for sensitive, emotive conversations with relatives. Participants were central to promoting connections between patients and their families at end of life and creating opportunities for a final contact before the death. However, the provision of support varied as a consequence of the pressures of the pandemic. Results are discussed under two themes: (1) challenges and facilitators to providing end of life care, and (2) support needs of relatives when a family member was dying during the COVID-19 pandemic. Conclusion: There is a need for flexible visiting arrangements at end of life during a pandemic. A systems-level approach is necessary to promote the wellbeing of health and social care professionals providing end of life care during and after a pandemic.